Management of Equality Package Teaching Staff in PKBM Global Mandiri - Rahmansyah, Citra Setya; Sulistyaningrum, Restu Dyah; Darmawan, Daddy; Lestari, Retno Dwi (Indonesian Journal of Adult and Community Education, 2024)
Non-formal education units through equivalency programs are an effortto provide justice for the entire community. In its implementation, the roleof teaching staff is certainly very influential on the quality of delivery ofknowledge and knowledge to students. Therefore, it is important tomanage the teaching staff. This study aims to examine how the process ofmanaging human resources, namely teaching staff at PKBMGlobal Mandiri.This research uses qualitative methods with data collection techniquesofinterviews and documentation. The result of this research is that themanagement of teaching staff at PKBM Global Mandiri is carried outtransparently, accountably, and democratically from the recruitmentprocess, development and training of teaching staff to the placement ofpositions and responsibilities, all of which are in line with the theory ofresource management which can be proven by the large number ofstudents and A accredited institutions